A deep kinematic survey of planetary nebulae in the Andromeda Galaxy - Merrett, Helen (2007)
This thesis presents a survey of compact emission-line objects in the Andromeda Galaxy (M31), performed using a novel new instrument, the Planetary Nebula Spectrograph. The final catalogue contains the positions, magnitudes and velocities for 3300 objects displaying [O III] emission at 5007 Angstroms, of which 2615 are found likely to be planetary nebulae (PNe) associated with M31. The survey area covers some 6 square degrees, taking in the whole of M31's disk out to a projected radius of 1.5 degrees, with extensions along the major and minor axes, and the Northern Spur and Southern Stream regions. The calibrated data have been checked for internal consistency and compared with other catalogues. With the exception of the very central, high surface brightness region of M31, this survey is complete to a magnitude limit of m(5007) ~ 23.75, 3.5 magnitudes into the planetary nebula luminosity function.